Efektivitas Metode Role Playing Terhadap Peningkatan Percaya Diri Siswa pada Pembelajaran IPS Kelas IV - Khasana, Nurul Uswatun; Imansyah, Farizal; Marleni, Marleni (Institut Teknologi Pendidikan Indonesia, 2022)
This research is quantitative research with experimental research methods. This study is focused on knowing the effectiveness of the use of the Role Playing learning method in increasing the confidence of class VI students in social studies learning. The problem behind this research is that in the implementation of learning the teacher still uses conventional learning methods and not only that, actually the teacher has also used various learning models such as discussion models. However, in practice, the teacher does not follow the procedure which makes it look like a normaldiscussion. Thus, the lack of interaction between teachers and students results in students becoming bored and not understanding the material being taught. The subjects in this study were class VI A and VI B. The instrument used in this study was a questionnaire distributed during the posttest and pretest, which consisted of 20 statements. If seen from the results of the t-test calculation with asignificant value is 0.000 <0.05, then H0 is rejected and Ha is accepted. So it can be concluded that there is a difference between the experimental pretest and posttest experimental learning outcomes, the researcher concludes that the role-playing learning method is effective in increasing students' self-confidence in social studies learning.